The triangle was translated 3 units to the right horizontally. (x+3, y)
You can just move one of the points to see how it moved.
Answer:
x = −1.24
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
−132.3x=165.1
Step 2: Divide both sides by -132.3.
![\frac{-132.3x}{-132.3} = \frac{165.1}{-132.3} \\](https://tex.z-dn.net/?f=%5Cfrac%7B-132.3x%7D%7B-132.3%7D%20%3D%20%5Cfrac%7B165.1%7D%7B-132.3%7D%20%5C%5C)
x= -1.247921
Answer:
(x+1)² + y² = 36
Step-by-step explanation:
<u>Equation of a circle:</u>
(x-h)² + (y-k)² = r²
Center: (h,k)
Radius: r
Given a center of (-1,0) and a radius of 6, we have for our equation:
(x-(-1))² + (y-0)² = 6²
(x+1)² + y² = 36
Answer: 3
Step-by-step explanation:
First, we will write a mathematical equation for the phrase given.
-> Let n be "a number"
four subtracted from twice a number is two
four subtracted from twice a number = 2
(twice a number) - 4 = 2
2n - 4 = 2
Now, we will solve this equation by isolating the variable.
2n - 4 = 2
2n = 6
n = 3
<em>Read more about </em><em>algebraic equations </em><em>here:</em>
<em>brainly.com/question/27791850</em>
Answer:
d=√(x2-x1)² + (y2-y1)²
Step-by-step explanation:
ans is √85 unit